THE ROLE OF YOUTH IN SHAPING ECOLOGICAL CULTURE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The role of youth in shaping ecological culture is of vital importance in today’s rapidly changing world. As the challenges of environmental pollution, climate change, and degradation of natural resources grow, the need for an informed and active new generation becomes ever more urgent. The concept of ecological culture involves not only knowledge and awareness of environmental issues, but also the development of values, behaviors, and attitudes that support sustainable living and the preservation of nature for future generations.